Front Crawl Technique of Rookie Swimmers Using the Front Crawl Technique Assessment - Azhar, Muhammad; Carsiwan, Carsiwan; Nugraha, Reshandi; Gumilar, Agus (JUMORA: Jurnal Moderasi Olahraga, 2025)
This study aims to analyze the most frequent freestyle swimming technique errors among elementary school rookie swimmers and examine how these errors affect swimming performance. A qualitative case study approach was used, utilizing the Front Crawl Technique Assessment instrument. The participants were 26 rookie swimmers who completed a 50-meter swim test, during which their technique errors and completion times were analyzed. The most frequent errors included kicking too deep, underreaching during entry, and lifting the head forward during inhalation. Pearson’s correlation analysis revealed a strong positive relationship between the number of technical errors and swim completion time (r = 0.95 for males; r = 0.93 for females, p < 0.01). This indicates that higher error rates were associated with slower swim times. These findings underscore the critical importance of technical precision in swimming performance and highlight the value of an objective assessment tool for evaluating and improving technique in young rookie swimmers. These results provide valuable guidance for coaches to design developmentally appropriate and targeted training programs that address specific technical weaknesses in rookie swimmers. Future researchers can build on these findings by testing whether targeted technique-correction programs accelerate skill acquisition in other swimming strokes or age groups